“The Advanced Prolong Montroller & Recording System” using Wireless, Distributed DAS Technology (International Journal of Engineering and Computer Science, 2014)
Almost in most industries there is a mounting need for high-ceilinged quality, efficiency and machine-plant environment monitoring systems. Moreover, so many industrial operation monitoring is necessary to record, analyze or control in order to have implementations of proper, cost-effective and wastage free or maintenance free Production and also to reduce repair/replacing strategies. Therefore, here “The Advanced Prolong Montroller & Recording System” using Wireless, Distributed DAS Technology is proposed as good, important system engineering.In this project, a wireless network for in-field operation, on time monitoring of multiple different area parameters like temperature, humidity is projected. The system network is arranged as able to sink operation-related data of remarkable areas to one central point, also called as master station. This master device is also automatically managing the communication with all remote monitoring stations distributed at different areas. Furthermore it will communicate with PC for data saving/recording & analyzing in the form of table & graphs.